TRANSLATION OF ANTROPONYMS AND PROBLEMS IN TRANSLATING THE ANTROPONYMS - Saitkhanova Aziza (Western European Studies, 2024)
This article discusses the translation of antroponyms: people’s names from English into Russian language, the article includes the information about lexical transformations used in translation people’s name.
Keywords: Translation; transcribtion; adequate; simultaneous